2020
DOI: 10.1007/s00167-020-06358-x
|View full text |Cite
|
Sign up to set email alerts
|

Medial stabilised total knee arthroplasty achieves comparable clinical outcomes when compared to other TKA designs: a systematic review and meta-analysis of the current literature

Abstract: Purpose The purpose of this study was to perform a systematic review and meta-analysis to compare clinical and patient-reported outcome measures of medially stabilised (MS) TKA when compared to other TKA designs. Methods The Preferred Reporting Items for Systematic Review and Meta-Analyses algorithm was used. The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and EMCARE databases were searched to June 2020. Studies with a minimum of 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…The WOMAC and HSS score after MP-TKA were significantly lower compared with PS-TKA, while there was no significant difference in KSS, KSFS, and OKS. Different from the previous three meta-analyses [ 12 , 14 , 15 ], we compared the position of two prosthesis. The analysis showed that the postoperative position of the prosthesis was good, and there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The WOMAC and HSS score after MP-TKA were significantly lower compared with PS-TKA, while there was no significant difference in KSS, KSFS, and OKS. Different from the previous three meta-analyses [ 12 , 14 , 15 ], we compared the position of two prosthesis. The analysis showed that the postoperative position of the prosthesis was good, and there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Different from previous meta-analyses [ 12 , 14 , 15 ],we paid more attention to the postoperative complication rate and revision rate of MP-TKA and PS-TKA. The study of Kim [ 21 ]et al was terminated early because of the high infection rate (6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first systematic review of RCTs that compared MP designs with conventional bearings, although meta-analysis was limited to comparison with PS bearings. Other systematic reviews and meta-analyses are limited by pooling of all study designs (retrospective and prospective), inclusion of study designs with a high risk-of-bias, pooling of all conventional bearing types into one group, and heterogeneity of included patients, 810 such as RCTs including both primary and revision procedures. 23 Notwithstanding, those reviews support our findings of no clear difference in clinical outcomes between MP and PS bearings.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported satisfactory clinical results of MP TKA ( Hossain et al, 2011 ; Youm et al, 2014 ; Steinbruck et al, 2016 ; Gray et al, 2020 ; Jones et al, 2020 ) and patient preference over PS and other prostheses ( Schmidt et al, 2003 ; Pritchett, 2011 ). On the contrary, other authors reported that the MP design was not superior to other designs in patient-reported outcomes and knee kinematics ( Chinzei et al, 2014 ; Papagiannis et al, 2016 ; Choi et al, 2017 ; Kim et al, 2017 ; Jones et al, 2020 ; Nisar et al, 2020 ). More evidence is needed to determine the effectiveness and design specialty of the MP prosthesis.…”
Section: Introductionmentioning
confidence: 89%